Penerapan Model Problem Based Learning dalam Mata Pelajaran Teknik Las SMAW untuk Meningkatkan Hasil Belajar Siswa - Yacob Rombe (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine the increase in student learning outcomes by applying the Problem Based Learning model to the subjects of the shield metal arc-welding technique in class XI welding SMKN 3 Palu. This classroom action research (CAR) consists of 2 cycles, each of which goes through the stages of planning, implementing, observing and reflecting. The subjects of this study were 32 students of class XI Las SMKN 3 Palu in the 2018/2019 academic year. The research instrument used was a test. The results of the research in the first cycle, the number of students who completed as many as 20 people with an average learning outcome of 72.06 and a classical percentage of 62.50. There is an increase in cycle II with students who complete learning has increased to 27 students, the average learning outcome is 85 and the classical percentage is 84.37%. There was an increase in the learning outcomes of class XI Las students with an increase in the percentage of 21.87% from cycle I to cycle II. The increase in learning outcomes occurred due to the application of the problem based learning model in the subject of SMAW welding techniques in class XI welding at SMKN 3 Palu.